On the Prospects for Child Disability Prevention Research - Alexander A. Baranov; Rimma N. Terleckaya (Вопросы современной педиатрии)
The presented review of the special literature data (on MEDLINE and eLIBRARY.RU databases) makes it possible to determine a number of topical issues for preventing child disability as well as trends of scientific research in this area, taking into account the causes of disability and its structure by the underlying disease. The World Health Organization has established a relentless focus on the problem of disability, including that of children, which is reflected in the continuous improvement of methods for assessing and classifying persistent disabilities. It has been shown that the prevention of disability in children and the support of families raising handicapped children and children with disabilities are among the main priorities of the state social policy of the Russian Federation. The data on modern technologies for reducing the genetic burden in the population from the perspective of prevention of hereditary and congenital diseases, including orphan ones, has been presented. The results of studies indicating the increasing role of the intestinal microbiota in the development and prevention of a number of diseases affecting the formation of disability in children have been presented. The problem of combating antibiotic resistance is considered from a preventive perspective. A number of scientific studies is devoted to non-infectious pathology, which is becoming increasingly important in the formation of disability in children of different age groups, starting from the neonatal period. The actual data on the role of obesity in the formation of serious health disorders has been given. The opinion is expressed on the need to create a system of hygienic and medico-psychological safety of children's life in conditions of hyperinformatisation and the modern environmental situation. It is assumed that the implementation of the results of the proposed research into health care practice will make it possible to influence the processes of disability in a child on a deeper pathogenetic level as well as to improve the arrangement of preventive activities in this direction.